2009
DOI: 10.1074/jbc.m804740200
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Hydrolysis of α- and β2-Adaptins Decreases Clathrin-dependent Endocytosis and May Promote Neurodegeneration

Abstract: Clathrin-dependent endocytosis is mediated by a tightly regulated network of molecular interactions that provides essential protein-protein and protein-lipid binding activities. Here we report the hydrolysis of the ␣-and ␤2-subunits of the tetrameric adaptor protein complex 2 by calpain. Calcium-dependent ␣-and ␤2-adaptin hydrolysis was observed in several rat tissues, including brain and primary neuronal cultures. Neuronal ␣-and ␤2-adaptin cleavage was inducible by glutamate stimulation and was accompanied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 48 publications
3
38
0
2
Order By: Relevance
“…Recent studies using yeast have indicated a role of PICALM in A␤ toxicity [113,114]. Changes in adaptor proteins decrease clathin mediated receptor endocytosis and sensitizes neurons to glutamate receptor excitotoxicity [115]. Together, these findings suggest that alterations in PICALM may affect iron metabolism, processing of A␤PP, endocytosis of receptors or exocytosis of neurotransmitters, with effects on neuronal excitation and excitotoxicity.…”
Section: Picalmmentioning
confidence: 81%
“…Recent studies using yeast have indicated a role of PICALM in A␤ toxicity [113,114]. Changes in adaptor proteins decrease clathin mediated receptor endocytosis and sensitizes neurons to glutamate receptor excitotoxicity [115]. Together, these findings suggest that alterations in PICALM may affect iron metabolism, processing of A␤PP, endocytosis of receptors or exocytosis of neurotransmitters, with effects on neuronal excitation and excitotoxicity.…”
Section: Picalmmentioning
confidence: 81%
“…The transferrin receptor is ubiquitously expressed and is known to undergo clathrin-mediated endocytosis with rapid recycling to the cell surface (26). PICALM, however, can selectively internalize some cargoes over others (20,27).…”
Section: Picalm and App Co-localize During Endocytosis In Vitro-mentioning
confidence: 99%
“…The absence of changes in sterol biosynthesis gene expression in primary striatal neurons exposed to mutant huntingtin fragments replicates previous data in this system and also concurs with previous microarray studies of human and mouse HD brains and microdissected neuronal samples (3). Our study used two different models with different time courses (3,4), and thus, the two different endpoints were reported. The observations of increased sterol accumulation through an apparently sterol regulatory element binding proteinindependent mechanism are also consistent with those of another independent study (5).…”
mentioning
confidence: 99%